POST ISLAMISME : TELAAH POLITIK TURKI MODERN ERA ERDOGAN - Alfikri, Lutfi Rosyad (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2022)
Turkey is one of the countries that adheres to a parliamentary and secular government system. The dynamics of Turkish political change fluctuate and continue to experience turmoil. This can be investigated at the time of the change in the government system that started from the monarchy to the Republic. Until the process of government embraced secular. Turkish secularism was imposed as a form of state anxiety and decline. It is because of this that a quarter of the world's territory is almost occupied. His character Mustafa Kemal Attatürk is considered the father of secularism. He later became an important figure in changing almost the entire flow of government and various policies that made Turkey a secular state. This means that there is an element of separation between the interests of the state and religion which was very strong in the Ottoman era. The Kemalist paradigm is total secularization, both in government and in life, in other words Turkey and upholds the concept of love for the homeland. In the discussion of this article, the topic of Turkish government is narrowed down by the Erdoan era. because according to the author's hypothesis in the era of Erdoan, the development of Islam in the government was growing rapidly.